Annals of the reformation and establishment of religion, and other various occurrences in the Church of England, during Queen Elizabeth's happy reign: together with an appendix of original papers of state, records, and letters - Strype, John (Benson collection of hymnals and hymnology, 1824)
v. 1, pt. 1. Introduction to this history. Annals of the reofrmation of religion under Queen Elizabeth -- v. 1, pt. 2. Annals ... An appendix; being a repository of faithful extracts out of various records and registers. Manuscripts made use of in these annals -- v. 2, pt. 1 Annals of the reformation of religion, and affairs of the church in this kingdom of England; From the twelfth year of the reign of Queen Elizabeth to the twenty-third -- v. 2, pt. 2. Annals ... Book 2. Appendis or original papers; referred to the annals. a catalogue of manuscripts and other old books made use of or cited in these annals, as well as in the former volume -- v. 3, pt. 1 Annals; being an history of the affairs of the Church of England: together with various other occurences of the state and kingdom coincident; chiefly with relation thereunto: continued; Book 1 -- v. 3, pt. 2. Annals ... Book 2. An appendix of original papers of state records, letters, &c. referred to in the foregoing annuals; Book 1-2 -- v. 4. Brief annals of church and state, under Queen Elizabeth. A supplement of records and original papers, to the former volumes of the annals; Serving to the further improving and illustrating of the history. Baker's manuscript notes on Strype's Annals.